Report on survey of legal education in CARICOM Member States : (draft) (IMPACT Justice Project, UWI Cave HillBB, 2017)
Conducts a survey of legal education to provide governments with information which can be used to shape policy in the CARICOM region. Considers a series of items including the purpose of legal education and revisits the West Indian System to see how thinking has changed since it was designed in the 1960s; whether the existing system is adequately meeting the needs of the region; the current system of administration to the law schools.
Keywords: LEGAL SCIENCES